(untitled) (Biomedical Research and Therapy, 2023)
Introduction: Cancer stem cells (CSCs) represent a distinct group of cells within cancerous tissue that possess the ability to initiate tumorigenesis and exhibit potency, self-renewal, and drug resistance. The study of CSCs often encounters challenges in obtaining these cells of interest or generating a sufficient quantity for downstream analysis. Nevertheless, it is feasible to enrich CSCs in vitro by subjecting them to conditions that stimulate their CSC properties, such as prolonged exposure to drugs or radiation, or by promoting their self-renewal capability through spheroid culture. Spheroids are a specific type of cell culture that organizes cells into a three-dimensional structure, closely mimicking the in vivo environment. These spheroids consist of a heterogeneous cell population, including CSCs or tumor-propagating cells responsible for tumor growth and maintenance. In our study, we cultured spheroids derived from single cells as well as multicellular aggregates to enrich CSCs based on their self-renewal capability and the structural organization provided by the three-dimensional context. Methods: Comparing the spheroid cultures with the parental adherent monolayer cells, we observed higher expression of CSC markers, pluripotent genes, and adipogenic differentiation in both multicellular spheroids (MCS) and single cell-derived spheroids (SCDS) of the two tested cell lines. Results: The spheroids exhibited progressive growth in size throughout the culture period. When comparing the two methods, SCDS demonstrated greater expression of surface markers and all three pluripotent genes associated with CSCs. Furthermore, when assessing drug resistance potential and the expression of the ABCG2 drug efflux gene, only 5637 SCDS displayed increased resistance to cisplatin and upregulation of ABCG2. Conclusion: In conclusion, both the MCS and SCDS methods effectively enriched the population of bladder CSCs in the 5637 and HT-1376 bladder cancer cell lines. However, the SCDS method demonstrated a higher upregulation of CSC markers and pluripotent gene expression compared to MCS. It is worth noting that spheroid culture and CSC enrichment are not mutually exclusive and can coexist with increased chemotherapy resistance and upregulation of ABCG2 drug efflux gene expression. Moreover, the drug efflux capability may vary depending on the specific cell line and clonal lineage. These strategies can serve as valuable models for CSC enrichment, the study of cancer cell behavior, disease modeling, and personalized chemotherapy investigations.